Role of Suppressor of Cytokine Signaling-1 In Murine Atherosclerosis - Grothusen, Christina (Public Library of Science, 2012)
BACKGROUND: While the impact of inflammation as the substantial driving force of atherosclerosis has been investigated in detail throughout the years, the influence of negative regulators of pro-atherogenic pathways on plaque development has remained largely unknown. Suppressor of cytokine signaling (SOCS)-1 potently restricts transduction of various inflammatory signals and, thereby modulates T-cell development, macrophage activation and dendritic cell maturation. Its role in atherogenesis, however has not been elucidated so far. METHODS AND RESULTS: Loss of SOCS-1 in the low-density lipoprotein receptor deficient murine model of atherosclerosis resulted in a complex, systemic and ultimately lethal inflammation with increased generation of Ly-6C(hi) monocytes and activated macrophages. Even short-term exposure of these mice to high-cholesterol dieting caused enhanced atherosclerotic plaque development with accumulation of M1 macrophages, Ly-6C positive cells and neutrophils. CONCLUSION: Our data not only imply that SOCS-1 is athero-protective but also emphasize the fundamental, regulatory importance of SOCS-1 in inflammation-prone organisms.